Soil-plant spectral diagnostic protocols for rapid and low-cost analysis of soil properties and plant nutrients using only light (infrared, x-rays) - CGIAR Research Program on Water, Land and Ecosystems (2019)
WLE/ ICRAF supported scaling the technology in Africa through the Africa Soil Information Service (AfSIS). In 2019 the technology went global, with major investments in China, Haiti, India, UK, USA, and elsewhere and a new initiative to develop a free global library and prediction service (see OICR #3337).